2021
DOI: 10.1051/0004-6361/202140991
|View full text |Cite
|
Sign up to set email alerts
|

Properties of slowly rotating asteroids from the Convex Inversion Thermophysical Model

Abstract: Context. Recent results for asteroid rotation periods from the TESS mission showed how strongly previous studies have underestimated the number of slow rotators, revealing the importance of studying those targets. For most slowly rotating asteroids (those with P > 12 h), no spin and shape model is available because of observation selection effects. This hampers determination of their thermal parameters and accurate sizes. Also, it is still unclear whether signatures of different surface material properties … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…We found our derived diameters and albedos to be broadly consistent with the NEATM-derived values with the WISE thermal data set (Mainzer et al 2019). Our derived thermal inertia were broadly consistent with the trends found with diameter (e.g., Delbo' et al 2007) and rotation period (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) in the literature, though in both cases the large uncertainties on thermal inertia limit the conclusions we were able to draw from the data. We applied a linear fit to the diameters and thermal inertia normalized to 1 au of the form log[Γ] = α + β log[D], we find best-fit values of α = 2.667 ± 0.059 and β = −0.467 ± 0.044 for our sample alone and α = 2.509 ± 0.017 and β = −0.352 ± 0.012 when combined with literature estimates.…”
Section: Conclusion and Future Prospectssupporting
confidence: 88%
See 2 more Smart Citations
“…We found our derived diameters and albedos to be broadly consistent with the NEATM-derived values with the WISE thermal data set (Mainzer et al 2019). Our derived thermal inertia were broadly consistent with the trends found with diameter (e.g., Delbo' et al 2007) and rotation period (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) in the literature, though in both cases the large uncertainties on thermal inertia limit the conclusions we were able to draw from the data. We applied a linear fit to the diameters and thermal inertia normalized to 1 au of the form log[Γ] = α + β log[D], we find best-fit values of α = 2.667 ± 0.059 and β = −0.467 ± 0.044 for our sample alone and α = 2.509 ± 0.017 and β = −0.352 ± 0.012 when combined with literature estimates.…”
Section: Conclusion and Future Prospectssupporting
confidence: 88%
“…Some earlier studies (e.g., Harris & Drube 2016) have suggested that slow rotators should present higher thermal inertia due to thermal observations being able to probe more deeply into an asteroid's surface. Other more recent studies (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) have found no excess of high thermal inertia values among slow rotators (conventionally defined as asteroids with P > 12 hours), nor for low thermal inertia values among fast rotators. In our sample, we likewise find thermal inertia values greater than 100 J m −2 s −0.5 K −1 to be generally present across our entire rotation period range, though we note that our sample is sparsely populated with rotation periods longer than 30 hours (Fig.…”
Section: Relationship With Rotation Periodmentioning
confidence: 85%
See 1 more Smart Citation
“…It was thus hypothesized that slow rotators (i.e., rotation periods longer than 12 hours) should on average present higher thermal inertia than those of fast rotators. While early studies such as Harris & Drube (2016) and Marciniak et al (2018) appeared to confirm this trend, later studies with larger samples of slow rotators (e.g., Marciniak et al 2019;Alí-Lagoa et al 2020;Marciniak et al 2021) found no such relation.…”
Section: Introductionmentioning
confidence: 95%
“…The orbital classification is sourced from the JPL Small-Body Database as one of the following: inner or outer MBAs (IMB: a < 2.0 au, MBA: 2.0 < a < 3.2 au, OMB: 3.2 < a < 4.6 au), Jupiter Trojans (TJN), Aten, Apollo, or Amor NEAs (ATE, APO, AMO), Mars crossers (MCA), or trans-Neptunian objects (TNO). The Marciniak et al (2021) results do not include the eight asteroids where only an upper limit was found for the thermal inertia.…”
Section: Introductionmentioning
confidence: 99%